Daily reading comprehension grade 5 - Gray, Amelia (Monterey, CA : Evan-Moor Corporation, 2010)
"The Evan-Moor Daily Reading Comprehension, Grade 5 Resource Book gives fifth graders direct instruction in important reading strategies, all aimed at improving reading skills. Our reading workbook fits well in the traditional classroom or for homeschooling, as it keeps gr. 5 children engaged with 150 original fiction and nonfiction reading passages. Some of the skills grade five students will learn include how to recognize the theme, characters, setting and main ideas. Our activities will help even reluctant readers gain the confidence they need to learn to enjoy reading, which can help them in all areas of their schooling."--Amazon
Primary
Keywords: Reading comprehension; Reading comprehension -- Problems, exercises, etc